Analysis Of The Suitability Of The Istisna' Agreement In Handmade Product Transactions On Tik Tok Shop: A Review Of Muamalah Fiqh - Suci Amelia Pratama; Moh. Idil Ghufron (CV Putra Publisher, 2026)
This study aims to analyze the suitability of handmade product transactions with the pre-order system at TikTok Shop against the principle of istisna' contracts in fiqh muamalah. The method used is descriptive qualitative with a literature study approach through the analysis of fiqh literature, fatwa, and previous research. The results of the study show that the practice of pre-order has basically reflected the elements of the istisna' contract, such as the agreement between the seller and the buyer, the object of the order, and the production process after the contract. However, the implementation is not fully optimal because there is still uncertainty in product specifications, completion times, and transaction mechanisms that have the potential to cause uncertainty (gharar). On the other hand, the escrow system and platform features help improve security, trust, and the balance of rights and obligations of the parties. Thus, the suitability of the istisna' contract is conditional, depending on the level of clarity and transparency in the transaction. Therefore, it is necessary to increase MSME actors' understanding of sharia principles and optimize the use of digital features so that transactions are more in accordance with the provisions of fiqh muamalah.